2020
DOI: 10.1523/jneurosci.1744-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Shared Neural Representations of Cognitive Conflict and Negative Affect in the Medial Frontal Cortex

Abstract: Influential theories of dorsal anterior cingulate cortex (dACC) function suggest that the dACC registers cognitive conflict as an aversive signal, but no study directly tested this idea. In this preregistered human fMRI study, we used multivariate pattern analyses to identify which regions respond similarly to conflict and aversive signals. The results show that, of all conflict-and value-related regions, only the dACC/pre-SMA showed shared representations, directly supporting recent dACC theories.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 58 publications
(51 reference statements)
1
25
0
Order By: Relevance
“…These studies show that cognitive and emotional tasks are processed on different, domainspecific levels (Imbir et al, 2020;Kunde et al, 2012;Soutschek & Schubert, 2013) and are dissociable on a neural level (i.e., a lateral prefrontal cognitive control mechanism and a rostral anterior cingulate emotional control mechanism (Egner et al, 2008). Furthermore, our results indicate that Emotional Stroop tasks may not evoke cognitive control through the need for suppression of the emotional distraction (Okon-Singer et al, 2013), because this would potentially lead to an interaction with control from Color Stroop tasks (yet see an alternative interpretation of Vermeylen et al, 2020). The present results also might be of interest to the debate whether the Emotional Stroop effect is a special type of Stroop effect Fig.…”
Section: Implications For Theoriesmentioning
confidence: 70%
See 2 more Smart Citations
“…These studies show that cognitive and emotional tasks are processed on different, domainspecific levels (Imbir et al, 2020;Kunde et al, 2012;Soutschek & Schubert, 2013) and are dissociable on a neural level (i.e., a lateral prefrontal cognitive control mechanism and a rostral anterior cingulate emotional control mechanism (Egner et al, 2008). Furthermore, our results indicate that Emotional Stroop tasks may not evoke cognitive control through the need for suppression of the emotional distraction (Okon-Singer et al, 2013), because this would potentially lead to an interaction with control from Color Stroop tasks (yet see an alternative interpretation of Vermeylen et al, 2020). The present results also might be of interest to the debate whether the Emotional Stroop effect is a special type of Stroop effect Fig.…”
Section: Implications For Theoriesmentioning
confidence: 70%
“…These findings of a functional segregation were in line with neuroimaging research that showed a separation between the rostral anterior cingulate cortex that is primarily involved in affective processing and regions of the dorsal anterior cingulate cortex and the lateral prefrontal cortex that were associated with nonemotional cognitive processes (Bush et al, 2000 ). In contrast, other theories question this separation and propose a close interaction between emotion and control (Dignath et al, 2020 ; Inzlicht et al, 2015 ; Pessoa, 2008 ; Shackman et al, 2011 ; Vermeylen et al, 2020 ) . For instance, Pessoa ( 2008 ) suggested that brain regions, such as the amygdala, the orbitofrontal cortex, and the anterior cingulate cortex, function as central hubs that integrate emotional and cognitive information (Pessoa 2008 ; for a meta-analysis see Shackman et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests a certain functional dissociation between these two closely located MFC clusters during affective task-switching. A recent multivariate pattern classification analysis of conflict and affect processing in the MFC showed that even though RCZ and pre-SMA share a similar voxel pattern for conflict processing and negative affect, processing of affect could be localized slightly more anteriorly (compare Figure 4 in Vermeylen et al, 2020). Since this contrast was based on affective versions of the Stroop and Eriksen Flanker tasks, this anterior (pre-SMA) region may have particular significance in modulating affective interference.…”
Section: Brain Mechanisms Underlying Asymmetric Switch Costsmentioning
confidence: 95%
“…In fact, conflict negativity may be instrumental in recruiting the mental resources required to cognitively resolve the conflict. Strong support for the notion of conflict as a negative signal comes from research that showed that individuals who perform the Stroop task also exhibit neural activity in brain regions that are associated with negativity (MacDonald et al, 2000;Kerns et al, 2004;Vermeylen et al, 2020). Other research that more directly investigated the conflict negativity hypothesis revealed that individuals who were exposed to Stroop conflict more quickly categorized subsequent negative words as negative (Dreisbach and Fischer, 2012), or were more likely to assign negative labels to subsequent stimuli (Fritz and Dreisbach, 2013; see also Goller et al, 2017).…”
Section: Conflict Negativitymentioning
confidence: 99%